Language education students' well-beings in online learning during the pandemic - Markus Budiraharjo; Veronica Triprihatmini; Christina Kristiyani (Master Program in Linguistics, Diponegoro University, 2022)
This study investigated perceived challenges and opportunities, as well as perceived impacts of policies (such as curricular ones) to mitigate the complex implications of Pandemic COVID-19 for the first year of language education students Batch 2020 of Sanata Dharma University. 58 students of the English Language and Education Study Program (ELESP) and the Indonesian Language and Literature Education Study Program (ILLESP) participated in this study. Both numerical and verbal data were gathered using Google Form survey. This study found a number of paradoxes faced by students. On the one hand, numerical data presents an optimistic outlook on how to maintain their well-being. On the other hand, the written expressions they wrote in the survey reveal a much more complex and challenging atmosphere.